2018
DOI: 10.1016/j.celrep.2018.10.093
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis Reveals Estrogen Signaling Coordinately Augments One-Carbon, Polyamine, and Purine Synthesis in Breast Cancer

Abstract: Highlights d Single-cell RNA-seq reveals estrogen-responsive genes in ERa+ breast cancer cells d Estrogen signaling induces a metabolic switch in breast cancer cells d Estrogen signaling coordinately augments one-carbon, polyamine, and purine synthesis d AZIN1 and PPAT are ERa targets that are essential for cell survival and growth

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
2
22
2
Order By: Relevance
“…In a similar manner, tRNA signalling is known to be an intracellular target of oestrogen, and an increased abundance of tRNA has been associated with proliferating cells 51,52 . Indeed, from the single-cell data, we observed the highest fraction of proliferative β cells in the PEG-insulin and GLP-1-oestrogen conjugate cotreated mice ( Fig.…”
Section: Ucn3mentioning
confidence: 95%
“…In a similar manner, tRNA signalling is known to be an intracellular target of oestrogen, and an increased abundance of tRNA has been associated with proliferating cells 51,52 . Indeed, from the single-cell data, we observed the highest fraction of proliferative β cells in the PEG-insulin and GLP-1-oestrogen conjugate cotreated mice ( Fig.…”
Section: Ucn3mentioning
confidence: 95%
“…PGC1α/ERRα directly represses several SGOCP enzymes downstream of the metformin-dependent activation of AMPK, which underlies the sensitivity of ERRα-positive (ER + ) breast cancer to the DHFR antagonist methotrexate (Audet-Walsh et al, 2016). Conversely, estrogens promote an ERα-dependent increase in polyamine and purine synthesis via metabolic reprogramming of the mitochondrial branch of the SGOCP (Zhu et al, 2018). Also in ER + breast cancer, targeting of ESRP1 down-regulates the lipogenic program and PHGDH expression and stops growth of endocrine-resistant breast cancer cells (Gökmen-Polar et al, 2019;Fig.…”
Section: The Sgocp Regulationmentioning
confidence: 99%
“…In spite of the high inter-patient heterogeneity, we identified that 4 stem cell quiescence-associated genes, ALDH1L1, HOPX, WNT5A and SOX9, were convergently hypomethylated in all the post-NAC samples. ALDH1L1 is a key enzyme that negatively regulate the one-carbon metabolism to limit cell proliferation [36, 37] and is a marker for quiescent neuron stem cells [23]. WNT5A is a non-canonical Wnt ligand and functions to maintain the quiescent state of multiple adult stem cells, such as hematopoietic stem cells [24] and neural stem cells [25].…”
Section: Discussionmentioning
confidence: 99%